SCIENTIFIC REASONING ABILITY OF CLASS XI STUDENTS OF SMA NEGERI 1 SINDUE TOMBUSABORA ON DYNAMIC FLUID MATTER - Isnawati, Isnawati; Sandi, Mohamad; Werdhian, I Komang; Giorgadze, Irma (EduFisika: Jurnal Pendidikan Fisika, 2024)
The purpose of this research is to determine the scientific reasoning abilities of students of state high school 1Sindue Tombusabora on dynamic fluid material. This type of research is qualitative research. The research respondents were 15 students out of 20 class XI Mathematics and Science 2 students at state high school 1 Sindue Tombusabora for the 2022/2023 academic year. The technique for taking respondents in this study used a purposive sampling area. The results of this study indicate that students' scientific reasoning on dynamic fluid material is still relatively low. This is evidenced by the category that students get the most in each scientific reasoning. In the pattern of correlation reasoning, students are in the No relationship (NR) category where most students are at (level 2) of the maximum (level 4) which means that students' correlation reasoning abilities to connect two problems or causation are still low. Then in the proportional reasoning pattern, most students are in the TM (no answer) category, where students do not answer questions, which means students empty answers (level 0). This means that the ability of students to provide answers to problems involving comparisons is still low.